MENERAPKAN KONSEP PERPUSTAKAAN 2.0 - Sudarsono, Blasius (BACA: Jurnal Dokumentasi dan Informasi, 2010)
The Library 2.0 terminology was coined in 2005 by Michael E Casey in his blog entitled Library Crunch. This article discusses the implementation of Library 2.0 concept, as a continuation of the previous article by the same author which had introduced the concept. Basically, Library 2.0 is an application of Web 2.0 for library purposes. It based on two fundament¬als that are: the strength of participation and the sophisticated of information technology. For library, theses forces based on three basic transformations i.e.: from book centered to human centered, from users oriented to users centered, and from information management to knowledge management. To discuss the implementation of the concept, the author did not start from the scratch, but looking other libraries that already had undertaken the effort. Examples are taken from USA, Australia, and China. Finally, the author discusses the possibility of Indonesian Librarians to implement the Library 2.0 concept. In addition the author also gives some suggestions.